Study on the liver Drug’s dominant metabolic enzymes for six effective components of the Huang qi Liuyi decoction - Wang, Qun; Tang, Tiantian; Wu, Zengguang; Yang, Hong; Gao, Yuan; Zhang, Shiyu; Song, Xinli; Chen, Xiaolan (Frontiers in Pharmacology, 2023)
To investigate the optimal metabolic enzymes of six effective components (astragaloside IV, glycyrrhizic acid, calycosin-glucuronide, formononetin, ononin, calycosin-7-O-β-D- glucoside) of Huangqi Liuyi Decoction. Methods: Mouse liver microsomes were prepared. The effects of six specific inhibitors on the metabolism of six effective components of Huangqi Liuyi decoction extract (HQD) were studied using liver microsomal incubation in vitro. Results: The chemical inhibitors of CYP2C37 inhibit the metabolism of glycyrrhizic acid and astragaloside IV. Formononetin and astragaloside IV metabolism is inhibited by the chemical inhibitors of CYP2C11. The chemical inhibitors of CYP2E1 and CYP1A2 inhibit the metabolism of calycosin-glucuronide. Chemical CYP3A11 inhibitors prevent formononetin and glycyrrhizic acid from being metabolized. However, no inhibitor significantly affected the metabolism of ononin and calycosin-7-O-β-D-glucoside. Conclusion: the above results indicated that CYP2C37 metabolizes astragaloside IV and glycyrrhizic acid, CYP2C11 metabolizes astragaloside IV and formononetin, CYP1A2 metabolizes calycosin-glucuronide, CYP2E1 metabolizes calycosin-glucuronide, and CYP3A11 metabolizes glycyrrhizic acid and formononetin. Furthermore, ononin and calycosin-7-O-β-D-glucoside appear to be metabolized by other phase I CYP450 enzymes or other pathways. This study provides an experimental basis for the study of pharmacokinetic differences caused by metabolic enzymes.